Winery website loyalty: the role of sales promotion and service attributes. Issue 2 (18th June 2018) - Pelet, Jean-Eric; Lecat, Benoît; Khan, Jashim; Rundle-Thiele, Sharyn; Lee, Linda W.; Ellis, Debbie; Wolf, Marianne McGarry; Kavoura, Androniki; Katsoni, Vicky; Wegmann, Anne Lena
Abstract : Purpose: This paper aims to examine the relationship between feelings toward buying wine on mobile phones and m-commerce website loyalty by examining the mediating role of sales promotion and the moderating role of service attributes of the m-commerce websites in influencing the mediation. Design/methodology/approach: A total of 3, 318 completed surveys were collected. Drawing on a large non-probability criterion-based purposive sample across six countries (France, Germany, Greece, South Africa, USA and Canada), mediation analysis was performed to examine the hypothesized relationships. Findings: Results show that sales promotion mediates the relationship between feelings toward buying wine on mobile phones and m-commerce website loyalty. Moderated mediation reveals that the indirect pathways (sales promotion) through which feelings toward buying wine over mobile exert its effect on m-commerce website loyalty are dependent on the value of service (wine delivery) attributes of the website. The results demonstrate that sales promotion and service are of paramount importance to wineries and wine marketers. Research limitations/implications: Wine producers and retailers should consider the use of sales promotion to enhance sales and loyalty to m-commerce websites. Practical implications: Wine producers and retailers should consider use sales promotion (such as SMS or push notifications) to enhance sales and influence consumer feelings and hence their loyalty. Originality/value: Wine m-commerce studies are limited, especially with an international perspective comparing six different countries: three from the old world (France, Germany and Greece) and three from the new world (North America with USA and Canada; and South Africa). Altogether, these six countries represent around 40 per cent of the world's wine consumption.